Farmer knowledge and willingness to pay for soil testing in Haiti. Issue 7 (9th July 2018) - Kokoye, Senakpon; Molnar, Joseph; Jolly, Curtis; Shannon, Dennis; Huluka, Gobena
Abstract : Purpose: The purpose of this paper is to investigate factors affecting farmers' perceptions and knowledge of soil testing benefits and fertilizers use in Northern Haiti. Design/methodology/approach: Data were collected from 452 farmers within 17 localities in Northern Haiti. The findings reveal that farmers currently have little or no knowledge of soil testing benefits and but know better about fertilizer use. The soil testing benefits and knowledge on fertilizers use were collected using Likert scale. Analyses were done using structural equations model and choice model. Findings: Factors such as farm size, participation in project, rice, banana and cocoa growers, affect farmers' perceptions and knowledge of soil testing benefits. Factors affecting willingness to pay include group membership, type of crops grown, whether farmer' land is on the slope, his farm size and whether he participates in the US Agency for International Development (USAID) project. Knowledge on fertilizer use is influenced by rice and banana growers, fertilizer use, participation in soil testing program and AVANSE/USAID. The effects of both latent variables are found to be positive but non-significant. Practical implications: As policy implication; farmers need training module to be better informed on soil testing benefits. Originality/value: Soil testing is a novel agricultural input that is being popularized in developing countries. For sustainability of the laboratory to be installed, this study is needed to fill the gap in research on farmers' behaviors toward and demand of soil testing in Northern Haiti.